Ultrassonografia para bloqueios periféricos em crianças: revisão sistemática e metanálise de ensaios clínicos randonizados - Cabral, Lucas Wynne [UNESP] (2015)
Background: it has been suggested that ultrasound-guided regional anesthesia could improve the blockade efficacy and decrease complication rates in the pediatric population, but this hypothesis has not previously been adequately tested in a quantitative manner. Aim: the purpose of this systematic review of randomized clinical trials (RCT) is to assess whether the use of ultrasonography in the pediatric population has advantages over any other method of nerve location, such as the anatomical landmark-based technique, paraesthesia or use of an electrical nerve stimulator. Methods: the systematic search, data extraction, critical appraisal and pooled analysis were performed according to the Cochrane Handbook and PRISMA guidelines. The search strategy included the CENTRAL of the Cochrane Library, Medline, EMBASE, and Lilacs. The date of the last search was November 5, 2014. The relative risk (RR), mean difference (MD) and their corresponding 95% confidence intervals (95% CIs) were calculated using the Revman statistical software for dichotomous and continuous outcomes, respectively. Results: eleven randomized, clinical, controlled trials (published between 2004 and 2013) with a total 634 patients met the inclusion criteria. The methodological quality of the included studies was considered regular. There was a slight benefit of ultrasound to the success rate (RR 1.19, 95% CI 1.07 to 1.33), which was variable according to the anatomical region studied and a more important reduction of the analgesia requirement in the postoperative period with the use of ultrasound for peripheral nerve blocks (RR 0.2, 95% CI 0.11-0.34). There was only one complication reported (blood vessel puncture in one control group). Conclusions: there is moderate evidence that the use of ultrasound-guided peripheral nerve block in children reduces the number of patients requiring additional analgesia in the postoperative period and ...